The Influence of Digital Marketing and Branding on Competitive Advantage of Culinary MSMEs in Bangkinang City - Hidayat, Rafi; Farhas, Rizqon Jamil (Civiliza Publishing, Indonesia., 2025)
Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector, play a vital role in local economic development but face increasing competition in the digital era. Limited market reach and weak brand identity remain key challenges that hinder their competitiveness. This study aims to examine the influence of digital marketing and branding on the competitive advantage of culinary MSMEs in Bangkinang City. The research employed a quantitative approach using a survey method, with data collected from 85 culinary MSME owners selected through purposive sampling. Primary data were analyzed using multiple linear regression with SPSS 25 to assess both partial and simultaneous effects of the independent variables. The results reveal that digital marketing and branding have a significant positive effect on competitive advantage, both individually and jointly. Digital marketing enhances market reach, customer engagement, and brand awareness, while branding strengthens brand identity, trust, and customer loyalty. Simultaneously, the integration of these strategies contributes to stronger product differentiation, improved market visibility, and sustainable competitiveness. In conclusion, effective and integrated implementation of digital marketing and branding is essential for improving the competitive position of culinary MSMEs in dynamic markets. This study contributes empirically by providing evidence on the strategic role of digital marketing and branding in strengthening MSME competitiveness and offers practical insights for MSME practitioners and policymakers in formulating sustainable business development strategies.